B Cell Anomalies in Autoimmune Retinopathy (AIR) - Stansky, Elena (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: Autoimmune retinopathy (AIR) is a retinopathy associated with unexplained vision loss presumably linked to circulating antiretinal antibodies; currently, however, there are no standardized criteria regarding the diagnosis, treatment strategy, or pathogenesis of this disease. The importance of B-lymphocyte immunophenotyping in the classification of AIR is unknown. METHODS: We utilized 15-color multiparametric flow cytometry to identify aberrations in B cell subsets that may contribute to the pathophysiology of AIR. Luminex cytokine analysis was also performed on plasma samples from AIR patients. RESULTS: Significant differences in AIR patients compared to individuals with other inflammatory conditions or healthy donors were found in the B cell memory compartment, including an increase in naïve B cells and a decrease in switched and unswitched memory B cells, which correlated with alterations in immunoglobulin secretion. CONCLUSIONS: These findings suggest that the maturation process of B cells may be impaired and that B cell immunophenotyping may help in understanding disease process in AIR.